IMPLEMENTASI LANDASAN HERMENEUTIKA DALAM STUDI ISLAM - Joni Putra; Rima Yuni Saputri; Diana (Journal of Islamic Education and Learning, 2021)
The background of this research is that there are problems in Islamic studies which include text and social studies, which of course must continue to be developed so that they have a wealth and variants of findings that will benefit scientific existence and have pragmatic benefits for society. The result of this research is that the hermeneutic approach in Islamic studies is seen as a tool in reading, understanding, a fact, the source text of Islamic teachings, both al-Qur'an and al-Hadith as well as the reality of social and religious behavior through an interpretation to express the true meaning of the text or reality.